KVPD E-Learning System - JANTAN, MUHAMMAD NAJMI AIMAN BIN JANTAN; Noraini Ibrahim, (Applied Information Technology And Computer Science, 2025)
The research addresses the need for enhancing the Kolej Vokasional Port Dickson (KVPD) E-Learning System by identifying and mitigating weaknesses inherent in the traditional KVPD learning method. Various challenges are identified, including the pace of teaching, financial burdens on students, accessibility of learning materials, and the assessment of students' skill levels.. To tackle these issues, the Prototyping Model with Evolutionary Prototyping is employed. Several key functionalities of the system are identified encompassing use cases  such as  login, register acoount, manage user, manage course, manage learning material, manage assessment and assignment, record grade and generate report. A comparative analysis of system features is conducted to pinpoint areas requiring improvement. The findings contribute significantly to refinemening E-Learning systems, fostering a more user-centric and efficient educational experience. The testing results demonstrate a successful implementation, with all criteria meeting or exceeding expected standards. Consequently, the system ensures heightened teacher involvement, alleviates financial strain on students, simplifies access to learning materials, and facilitates accurate assessment of students' skill levels. In conclusion, the study underscores the importance of continuous evolution in educational technology. Insights gained pave the way for future research endeavors aimed at further enhancing E-Learning systems, thereby enriching the educational landscape.